O processo de socialização profissional dos professores de música da cidade de Manaus - Amazonas - Moreira, Dulcianne da Silva (2024)
The aim of this study was to present the socializing agents before, during and after the professional training of music teachers in the city of Manaus-AM. The research was characterized as descriptive, exploratory and cross-sectional, with a qualitative approach to data analysis. The subjects investigated were music teachers working in public or private schools. Data was collected using questionnaires and a semistructured interview. The qualitative data analysis followed the guidelines of Bardin (2011), who divided the process into three stages: pre-analysis, a general organization of the documents collected, consisting of the corpus of the research; exploration of the material, being the systematic application of the decisions made in the first stage; and treatment of the results, in which the cut was made, that is, the coding of the research. The results were based on the understanding that the socialization process did in fact help to bring them closer to music, to choose a music degree and to work in music education. This shows in practice that professional socialization really does cover the subject's entire life and shapes their understanding of themselves as professionals through social interactions throughout their lives.